Conceptual design of an efficient unified shunt active power filter based on voltage and current source converters. (15th January 2017) - Zafari, A.; Jazaeri, M.
Abstract: This paper establishes a detailed design of a novel structure of Unified Shunt Active Power Filter (USAPF) in which both Voltage Source Converter (VSC) and Current Source Converter (CSC) operate simultaneously (VCSC scheme). In this unified scheme, separation of the frequency components of the reference current and dedication of low orders to the CSC section and high orders to the VSC section is the key point of the idea. The separation frequency based on a criterion is first computed, and then the contributions of CSC and VSC sections are determined. It is mathematically shown that such allocations can guarantee the minimization of the total active power losses of the unified filter among different types of allocations. The design procedure is initiated with deriving allowable operating ranges for the passive elements in dc and ac sides of the converters and continued to find the switching frequency for both converters. Simulation and experimental results not only confirm the correctness of the design, but also show the values of the passive elements become significantly lower than the values found in CSC and VSC based APF alone. This reduction can lead to a considerable reduction in overall losses in the VCSC scheme. Highlights: The proposed unified SAPF (USAPF) has all merits of CSC and VSC based SAPF. Simulation results show the validity of design procedure. An efficient situation has been selected in design procedure of USAPF. Passive elements' size is less than it in conventional APF.